O Fundamento Do Especulativo: Hegel E O Conceito Como Vida, Seu Desenvolvimento Na Linguagem E Sua Realização Nas Primeiras Formas Sociais. - Lion, Thiago Ferreira [UNIFESP] (2018)
This Work Aims To Demystify Hegel's Theory And Present The Concrete Foundation Of Speculative Thought. It Is Analyzed Here Not As Mere Thinking, But As An Effective Unfolding Of The Contradiction Which Is Its Condition Of Existence. It Begins With The Living Being With Its Dialectic Between Body And Abstraction (Life), And After Deals With The Development Of Perception And Then Enters Into The Analysis Of The Understanding Operating As A System Of Linguistic Value. Finally We Will See These Forms In Action In The Early Social Structures. Dividing These Moments It Becomes Possible To Isolate Aspects Of Hegel's Theory And To Compare Them With Central Developments Of Specific Theories Of Each Of These Areas (Mainly Of Aristotle, Marx, Saussure, Jakobson, Lacan, Freud, Mauss, Durkheim And Lévi-Strauss). It Makes It Easier Not Only To Dispel The Accusations Of Mysticism But Also To Glimpse How Hegel's Thought Could Anticipate So Many Aspects Of Later Theories.